Femoral Nerve Block and Intravenous Fentanyl for Positioning During Spinal Anesthesia in Surgery of Femur Fractures: Hemodynamic Changes - Vijay Siddhartha B S; Ranjini BN (Academia Anesthesiologica International, 2020)
Background: Fentanyl is a synthetic opioid and a phenylpiperidine derivative. It is structurally related to Pethidine, and is 75-125 times as potent as Morphine. It is a potent lipophilic opioid. It is a ? receptor agonist with a short onset time and moderate Duration of action. Fentanyl citrate is N-(1-phenethyl-4-piperidinyl) propionanilidedi hydrogen citrate. Subjects and Methods: A pre-anesthetic evaluation comprising of history of previous medical and surgical illnesses, previous anesthesia exposures, drug allergies and upper respiratory tract infection; clinical examination and baseline investigation of blood hemoglobin, radiograph of the chest and airway examination was done.. Results: Heart rate, systolic and diastolic BP after 20 minute within and between groups. T test was applied to find any statistical difference between the groups. The statistical test showed that there was a significant difference in heart rate, systolic and diastolic blood pressure between the two groups with p value less than 0.05. Conclusion: It is found that heart rate, systolic and diastolic BP start decreasing with femoral nerve block after 10th minute. No difference in hemodynamic changes found in fentanyl group.